Exploring Online Teaching Strategies and Implications: A Narrative Study Of Pre-Service Efl Teachers During Teaching Practicum - Supiani Supiani; Aulia Fatmawati; Fitra Ramadani (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study explored the instructional strategies employed by pre-service English as a Foreign Language (EFL) teachers during their online teaching practicum and examined their implications for student learning and teacher development. Adopting a narrative qualitative approach, data were collected through semi-structured interviews and field notes involving four pre-service EFL teachers and analyzed thematically. The findings revealed that participants implemented a range of instructional strategies, including discovery learning, expository learning, inquiry learning, contextual teaching and learning (CTL), cooperative learning, brainstorming, and thinking skills-based learning. Strategy selection was influenced by instructional objectives, students’ learning needs, and the demands of online teaching. Participants perceived that these strategies promoted students’ cognitive engagement, critical thinking, collaboration, participation, and comprehension by encouraging active interaction and connecting learning to authentic contexts. The findings also indicated positive implications for pre-service teachers, including enhanced pedagogical competence, classroom management, instructional organization, reflective practice, and confidence in online teaching. Furthermore, the practicum enabled participants to integrate theoretical knowledge with authentic teaching experience under mentor guidance. These findings underscore the importance of strengthening teacher education programs by integrating diverse pedagogical approaches and digital competencies to prepare future teachers for effective technology-mediated instruction.